If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(4x + m) = 5(x + 6) Reorder the terms: 8 + -1(m + 4x) = 5(x + 6) 8 + (m * -1 + 4x * -1) = 5(x + 6) 8 + (-1m + -4x) = 5(x + 6) Reorder the terms: 8 + -1m + -4x = 5(6 + x) 8 + -1m + -4x = (6 * 5 + x * 5) 8 + -1m + -4x = (30 + 5x) Solving 8 + -1m + -4x = 30 + 5x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -1m + -8 + -4x = 30 + -8 + 5x Reorder the terms: 8 + -8 + -1m + -4x = 30 + -8 + 5x Combine like terms: 8 + -8 = 0 0 + -1m + -4x = 30 + -8 + 5x -1m + -4x = 30 + -8 + 5x Combine like terms: 30 + -8 = 22 -1m + -4x = 22 + 5x Add '4x' to each side of the equation. -1m + -4x + 4x = 22 + 5x + 4x Combine like terms: -4x + 4x = 0 -1m + 0 = 22 + 5x + 4x -1m = 22 + 5x + 4x Combine like terms: 5x + 4x = 9x -1m = 22 + 9x Divide each side by '-1'. m = -22 + -9x Simplifying m = -22 + -9x
| 9m-14-6m+4r+12r= | | 7x+14-2x-5=3x+9+2x | | (x+6)(x+3)=340 | | 4(a+3)=2a-12 | | -25d+2s-7+15s-20d= | | -11a^2b*8ab= | | 7x+14-2x-5=3x | | 7x+14-2x-5=3x | | 5a*a^2= | | 2(x+6)=9x+9-7x+3 | | 3a^2-3a= | | 20j+20j-16m-16m+16= | | 6k-(4k+2)-8+8(2k+2)=0 | | x-5=28 | | 6k-(2k+2)-8+8(2k+2)=10 | | 6k-(4k+2)-8+8(2k+2)=10 | | 10+(-4g)+10-13x-2g+5x= | | 2.75=f-.25 | | 3x-15+10x=13x+20 | | 5y+7=1-7y | | -19m+5-(-m)+c-7c= | | 7x-4+3x+12= | | 7x-4+3x+12=30 | | 3x+(-17)+21f+3x-(-21f)= | | 3y-20+y+40=120 | | 3y-20+y+40=180 | | 3y-20+y+40=90 | | 3y-20+y+40=30 | | 3x-20+x+10=30 | | 3(3m-4)-(2m-3)=m+9 | | 3x-20+x+10=90 | | 3x-20+x+10= |